Comparison of Differentially Expressed Genes in Human and Canine Osteosarcoma - Jorja Jackson-Oxley; Aziza A. Alibhai; Jack Guerin; Rachel Thompson; Rodhan Patke; Anna E. Harris; Corinne L. Woodcock; Dhruvika Varun; Maria Haque; Tinyiko K. Modikoane; Amber A. Kumari; Jennifer Lothion-Roy; et al. (Life)
Osteosarcoma (OSA) is the most prevalent bone malignancy in people and dogs. Current survival rates show the need for advances in novel therapies to help overcome the growth, survival and metastatic progression of the cancer. Canine models are often used to advance prognostic and treatment opportunities for OSA due to the similarities in the disease between species. This study focusses on the genetic and molecular similarities of OSA between human and canine specimens. Differentially expressed genes (DEGs) were compared and identified in canine and human OSA tumours, revealing 86 common genes, 36 having high and 50 having low expression. Further immunohistochemical analysis of the corresponding proteins of three identified DEGs (ASPN, STK3, BAMBI) allowed for the visualisation of protein expression in canine OSA tissues (n = 19). Overall nuclear and cytoplasmic H-scores were generated, and nuclear and cytoplasmic scores in males and females and in different anatomical locations (axial versus appendicular) were also investigated, presenting unique opportunities to understand the expression in this cancer type. This study contributes to a deeper knowledge of genetic pathways changes and identifies avenues for the diagnosis, prognosis and treatment of OSA in people and dogs, whilst encompassing the One Health concept in medicine.